Antipyretic Activity of Spare Leaf Extract (Erythrina subumbrans (Hassk.) Merr.) on Pepton-Induced Male White Rats (Rattus norvegicus) - Respia Mandasari; isra Thristy (Jurnal Kesehatan dan Kedokteran, 2026)
Fever is a common physiological response of the body to infection, inflammation, or other pathological conditions and is characterized by an increase in body temperature above the normal range. Although antipyretic drugs such as paracetamol are widely used to reduce fever, the exploration of medicinal plants as alternative natural antipyretic agents remains important. Dadap serep leaves (Erythrina subumbrans (Hassk.) Merr.) are known to contain bioactive compounds such as flavonoids, saponins, tannins, alkaloids, and polyphenols, which are potentially associated with antipyretic and anti-inflammatory activity. Objective: This study aimed to evaluate the antipyretic activity of dadap serep leaf extract in peptone-induced male white rats (Rattus norvegicus) and to determine the most effective dose among 100, 200, and 400 mg/kgBW. Methods: This research was a laboratory experimental study using a pre-test and post-test control group design. A total of 30 male white rats were divided into five groups: negative control receiving 1% Na-CMC, positive control receiving paracetamol, and three treatment groups receiving dadap serep leaf extract at doses of 100, 200, and 400 mg/kgBW. Fever was induced by subcutaneous injection of 5% peptone, and rectal body temperature was measured at several observation times after treatment. Data were analyzed using One-Way ANOVA followed by the Tukey HSD post hoc test. Findings: The results showed that dadap serep leaf extract reduced rectal body temperature in peptone-induced rats. The strongest antipyretic effect was observed at a dose of 400 mg/kgBW, indicating that higher extract doses may produce a greater reduction in fever temperature. Implications: These findings indicate that dadap serep leaf extract has potential as a natural antipyretic agent and may support the development of plant-based fever management. The results may also provide a scientific basis for the traditional use of dadap serep leaves in reducing fever. Originality: The originality of this study lies in providing experimental evidence on the dose-dependent antipyretic effect of Erythrina subumbrans leaf extract in a peptone-induced fever model of male white rats.